Graphite composite negative electrode material, and preparation method and application thereof

CN116825977BActive Publication Date: 2026-10-27TSINGHUA UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210282558.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-22
Publication Date
2026-10-27
Estimated Expiration
2042-03-22

AI Technical Summary

Technical Problem

但同时,该类负极材料依旧存在易团聚、粉化现象,首次效率低,充放电过程中体积发生严重膨胀(膨胀倍率约355%)而造成电池结构的破坏,这严重制约了锡基负极材料及硅基负极材料的进一步发展

Benefits of technology

[0024]1、本发明提供的制备石墨复合负极材料的方法中,通过对石墨进行微膨改性的同时,实现与锡基材料或硅基材料复合,使锡基材料或硅基材料嵌入到改性后的石墨片层间及粘附在改性石墨表面,最后通过包覆处理,得到微膨改性石墨/锡基材料或硅基材料/碳包覆的石墨复合负极材料,有效提高了含锡基负极材料或含硅基负极材料的石墨复合负极材料的比容量和循环稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116825977B_ABST
    Figure CN116825977B_ABST
Patent Text Reader

Abstract

The application provides a graphite composite negative electrode material and a preparation method and application thereof. In a liquid phase system, graphite is slightly expanded, and tin-based material or silicon-based material is embedded between layers of the slightly expanded graphite. After carbon coating, the graphite composite negative electrode material with a carbon coating layer is obtained. The tin-based material or silicon-based material is embedded between layers of the slightly expanded graphite and adhered to the surface of the slightly expanded graphite, which effectively improves the specific capacity of the composite negative electrode material, uniformly disperses the tin-based material or silicon-based material, and avoids aggregation of the tin-based material or silicon-based material in the cycle process. Meanwhile, the sandwich structure formed by the tin-based material or silicon-based material dispersed between layers of the graphite can relieve the volume expansion of the tin-based material or silicon-based material in the charge and discharge process and provide the required space for the expansion. The carbon coating layer can avoid consumption of the electrochemical side reaction between the active material and the electrolyte, improve the cycle performance and the initial coulomb efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery materials technology, specifically to a graphite composite anode material, its preparation method, and its application. Background Technology

[0002] With the introduction of national policies related to electric vehicles and other fields, lithium-ion batteries will account for an increasingly larger proportion in future mobile devices and large-scale energy storage, which also places higher demands on the performance of lithium-ion batteries. The negative electrode material of lithium-ion batteries is one of the key materials determining battery performance. Graphite, due to its high electronic conductivity, high lithium intercalation capacity, low lithium intercalation potential, and small volume change before and after lithium intercalation and deintercalation, has become a widely used negative electrode material in the current market.

[0003] However, due to its inherent structural limitations, graphite has encountered bottlenecks as a negative electrode material. Its capacity in market applications has reached its limit, failing to meet the demands of high-current charging and discharging in power batteries. Therefore, with the increasing demand for energy density, tin-based and silicon-based negative electrodes, possessing high theoretical specific capacity, have been extensively studied. These negative electrode materials exhibit lower lithium insertion / extraction potentials (slightly higher than graphite), are less prone to lithium dendrite formation, and offer better safety. However, they still suffer from agglomeration and pulverization, low initial efficiency, and severe volume expansion during charging and discharging (approximately 355% expansion rate), which can damage the battery structure. This significantly restricts the further development of tin-based and silicon-based negative electrode materials.

[0004] Therefore, it is of great research significance to adopt effective methods to modify the above-mentioned materials to make up for their defects and obtain composite anode materials with high initial coulombic efficiency, small volume effect and stable cycling. Summary of the Invention

[0005] To address the technical problems existing in the aforementioned related technologies, this application provides a graphite composite anode material, its preparation method, and its application. By micro-expanding and modifying graphite, it achieves composite with tin-based or silicon-based materials, allowing the tin-based or silicon-based materials to be embedded between the micro-expanded graphite flakes and adhered to the surface of the modified graphite. Finally, through coating treatment, a graphite composite anode material coated with micro-expanded modified graphite / tin-based material or silicon-based material / carbon is obtained, effectively improving the specific capacity and cycle stability of the graphite composite anode material containing tin-based or silicon-based anode materials.

[0006] The details are as follows:

[0007] In a first aspect, the present invention provides a method for preparing a graphite composite anode material, the method comprising the following steps:

[0008] S1. Under ice-water bath conditions, graphite and tin-based materials are mixed with concentrated sulfuric acid, or graphite and silicon-based materials are mixed with concentrated sulfuric acid to obtain a mixed slurry;

[0009] S2. Add hydrogen peroxide dropwise to the mixed slurry, stir evenly, place it in an oven at 25℃-55℃ and let it stand for 3h-15h, then wash with water, filter and dry to obtain an intermediate containing tin-based or silicon-based materials between graphite flakes.

[0010] S3. After thoroughly mixing the intermediate containing tin-based or silicon-based materials between the graphite sheets with the coating material, carbonize and cool to obtain a graphite composite anode material.

[0011] Optionally, in step S1, the graphite is flake graphite;

[0012] The tin-based material is tin disulfide or tin dioxide;

[0013] The silicon-based material is silicon or silicon oxide.

[0014] Optionally, the flake graphite is natural flake graphite, or spherical graphite formed by spherizing natural flake graphite.

[0015] Optionally, in step S1, the mass ratio of graphite to tin-based material is 1:5.1-1, or the mass ratio of graphite to silicon-based material is 1:5.1-1.

[0016] The mass-volume ratio of the graphite to the concentrated sulfuric acid is 1g:5mL-25mL.

[0017] Optionally, in step S2, the volume ratio of concentrated sulfuric acid to hydrogen peroxide is 1:5.1-5.4.

[0018] Optionally, in step S3, the coating material is one or more of polydopamine, polyvinylpyrrolidone, asphalt, and graphene oxide.

[0019] Optionally, in step S3, the coating material accounts for 1%-55% of the mass of the graphite composite anode material obtained after coating.

[0020] Optionally, in step S3, the carbonization temperature is 455℃-1555℃, and the carbonization time is 1h-3h.

[0021] In a second aspect, the present invention provides a graphite composite anode material, which is prepared according to the preparation method described in the first aspect above.

[0022] Thirdly, the present invention provides an application of a graphite composite anode material, wherein the graphite composite anode material prepared by the preparation method described in the first aspect is applied to a lithium-ion battery.

[0023] Compared with related technologies, the graphite composite anode material, its preparation method, and its application provided in this application have at least the following advantages:

[0024] 1. In the method for preparing graphite composite anode materials provided by the present invention, graphite is micro-expanded and modified while being composited with tin-based or silicon-based materials. The tin-based or silicon-based materials are embedded between the layers of the modified graphite sheets and adhered to the surface of the modified graphite. Finally, through a coating process, a graphite composite anode material coated with micro-expanded modified graphite / tin-based material or silicon-based material / carbon is obtained, which effectively improves the specific capacity and cycle stability of the graphite composite anode material containing tin-based or silicon-based anode materials.

[0025] 2. The composite anode material obtained by the method provided by this invention enables tin-based or silicon-based materials to be embedded between layers of micro-expanded modified graphite sheets and adhered to the surface of the micro-expanded modified graphite, thus dispersing the tin-based or silicon-based materials and preventing agglomeration during cycling. Simultaneously, the sandwich structure formed by the dispersion of tin-based or silicon-based materials between the graphite sheets can alleviate the volume expansion of the tin-based or silicon-based materials during charging and discharging and provide the necessary space for their expansion. Further carbon coating can effectively reduce the direct contact between the active material in the carbon anode material and the electrolyte in the battery, avoiding electrochemical side reactions between the active material and the electrolyte that would lead to consumption, improving cycle performance and initial coulombic efficiency, and maintaining the stability of the material structure. Attached Figure Description

[0026] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0027] Figure 1 A flowchart illustrating the preparation method of graphite composite anode material in an embodiment of the present invention is shown;

[0028] Figure 2 A low-magnification scanning electron microscope image of the graphite composite anode material in an embodiment of the present invention is shown;

[0029] Figure 3 High-magnification scanning electron microscope images of the graphite composite anode material in an embodiment of the present invention are shown;

[0030] Figure 4The graphite composite anode material in Example 1 of this invention is shown in 155 mAh g. -1 Electrochemical performance curves at current density;

[0031] Figure 5 The graphite composite anode material in Example 1 of this invention is shown in a 1555 mAh g⁻¹. -1 Cyclic curves at current density;

[0032] Figure 6 The graphite composite anode material in Example 4 of this invention is shown in 155 mAh g. -1 Electrochemical performance curves at current density;

[0033] Figure 7 The graphite composite anode material in Example 4 of this invention is shown in a 1555 mAh g⁻¹ solution. -1 Cyclic curves at current density;

[0034] Figure 8 The graphite composite anode material in Example 5 of this invention is shown in 155 mAh g. -1 Electrochemical performance curves at current density. Detailed Implementation

[0035] The following embodiments are provided to better understand the present invention and are not limited to the preferred embodiments described. They do not constitute a limitation on the content and scope of protection of the present invention. Any product that is the same as or similar to the present invention, derived by any person under the guidance of the present invention or by combining the features of the present invention with other prior art, falls within the protection scope of the present invention.

[0036] Specific experimental steps or conditions are not specified in the examples; however, they can be performed according to the conventional experimental steps or conditions described in the prior art. Reagents and other instruments used, unless otherwise specified, are all commercially available conventional reagent products.

[0037] To maximize the capacity performance of carbon anode materials, reduce their charge-discharge expansion rate, and improve cycle performance, this application proposes the following technical concept: Simultaneously, tin-based or silicon-based materials are embedded between the micro-expanded graphite sheets in a liquid-phase system to achieve micro-expansion of graphite. Then, the graphite containing tin-based or silicon-based materials in the gaps and on its surface is carbon-coated, resulting in a graphite composite anode material with a carbon-coated layer. The embedding of tin-based or silicon-based materials between the micro-expanded modified graphite sheets and their adhesion to the surface of the micro-expanded modified graphite effectively improves the specific capacity of the composite anode material and ensures uniform dispersion of the tin-based or silicon-based materials, preventing agglomeration during cycling. Furthermore, the sandwich structure formed by the dispersion of tin-based or silicon-based materials between the graphite sheets alleviates the volume expansion of the tin-based or silicon-based materials during charge-discharge and provides the necessary space for their expansion. It effectively improves cycle stability; the carbon coating layer can effectively reduce the direct contact between the active material in the carbon anode material and the electrolyte in the battery, avoid the electrochemical side reactions between the active material and the electrolyte and thus avoid consumption, thereby improving cycle performance and first coulombic efficiency.

[0038] Based on the above technical concept, this application provides a carbon anode material, its preparation method, and its application.

[0039] In a first aspect, the present invention provides a method for preparing a graphite composite anode material. Figure 1 A flowchart illustrating the preparation method of the graphite composite anode material in an embodiment of the present invention is shown. Figure 1 As shown, the preparation method includes the following steps:

[0040] S1. Under ice-water bath conditions, graphite and tin-based materials are mixed with concentrated sulfuric acid, or graphite and silicon-based materials are mixed with concentrated sulfuric acid to obtain a mixed slurry;

[0041] S2. Add hydrogen peroxide dropwise to the mixed slurry, stir evenly, and then place it in an oven at 25℃-55℃ for 3h-15h. Then wash with water, filter and dry to obtain an intermediate containing tin-based or silicon-based materials between the graphite flakes.

[0042] In this implementation step, under ice-water bath conditions, sulfuric acid molecules insert into the interlayer of graphite flakes, forming a graphite intercalation compound. At temperatures of 25℃-55℃, the flake graphite undergoes micro-expansion modification under the action of concentrated sulfuric acid and hydrogen peroxide. Simultaneously, since the mixed slurry also contains tin-based or silicon-based materials, these materials, along with the sulfuric acid, enter the interlayer of the graphite flakes. Subsequently, water washing, filtration, and drying are performed to remove the sulfuric acid, yielding an intermediate containing tin-based or silicon-based materials in the interlayer of the graphite flakes.

[0043] In this process, tin-based or silicon-based materials are embedded between the layers of micro-expanded modified graphite sheets and adhered to the surface of the micro-expanded modified graphite. This effectively improves the specific capacity of the composite anode material and ensures uniform dispersion of the tin-based or silicon-based materials, preventing agglomeration during cycling. Simultaneously, the sandwich structure formed by the dispersion of tin-based or silicon-based materials between the graphite sheets mitigates the volume expansion of the tin-based or silicon-based materials during charging and discharging, providing the necessary space for expansion and effectively improving cycle stability. S3. After thoroughly mixing the intermediate containing tin-based or silicon-based materials between the graphite sheet layers with the coating material, carbonization and cooling are performed to obtain the graphite composite anode material.

[0044] In this implementation step, the intermediate containing tin-based or silicon-based materials between the graphite sheets is further coated to effectively reduce the direct contact between the active material in the carbon anode material and the electrolyte in the battery, avoid electrochemical side reactions between the active material and the electrolyte that would lead to consumption, thereby improving cycle performance and first coulombic efficiency.

[0045] Optionally, in step S1, the graphite is flake graphite;

[0046] Tin-based materials are tin disulfide or tin dioxide;

[0047] Silicon-based materials are silicon or silicon oxide.

[0048] Optionally, the flake graphite is natural flake graphite, or spherical graphite formed by spheroidizing natural flake graphite.

[0049] Optionally, in step S1, the mass ratio of graphite to tin-based material is 1:5.1-1, or the mass ratio of graphite to silicon-based material is 1:5.1-1;

[0050] The mass-volume ratio of graphite to concentrated sulfuric acid is 1g: 5mL-25mL.

[0051] Optionally, in step S2, the volume ratio of concentrated sulfuric acid to hydrogen peroxide is 1:5.1-5.4.

[0052] Optionally, in step S3, the coating material is one or more of polydopamine, polyvinylpyrrolidone, asphalt, and graphene oxide.

[0053] Optionally, in step S3, the coating material accounts for 1%-55% of the mass of the graphite composite anode material obtained after coating.

[0054] Optionally, in step S3, the carbonization temperature is 455℃-1555℃, and the carbonization time is 1h-3h.

[0055] In a second aspect, the present invention provides a graphite composite anode material, which is prepared according to the preparation method of the first aspect described above.

[0056] In specific implementation, this invention achieves the embedding of tin-based or silicon-based materials into graphite sheets during the micro-expansion process of graphite at room temperature, followed by carbon coating, to obtain a spatially confined composite anode material. The micro-expansion modified graphite and carbon coating can mitigate the volume changes of tin-based or silicon-based materials during charge and discharge, maintaining a stable SEI film. Simultaneously, the dispersion of tin-based or silicon-based materials on the surface and between the sheets of micro-expansion modified graphite effectively alleviates particle agglomeration, enhances dispersibility, and reduces capacity decay. Carbon coating further improves the material's conductivity, prevents side reactions between the electrolyte and active materials, improves the material's initial coulombic efficiency, and maintains structural stability. This composite anode material exhibits advantages such as high capacity, excellent cycle performance, and suitability for high-rate charge and discharge in lithium-ion batteries.

[0057] Thirdly, the present invention provides an application of a graphite composite anode material, wherein the graphite composite anode material prepared by the preparation method described in the first aspect is applied to a lithium-ion battery.

[0058] In practice, the preparation process of this invention is simple and low-cost, and the prepared materials are suitable for large-scale production. The resulting composite anode material exhibits excellent electrochemical performance when used as an anode material for lithium-ion batteries. Compared with commercial graphite, the capacity and rate performance of the obtained anode material are significantly improved, and it also has better cycle stability at high current densities.

[0059] To enable those skilled in the art to better understand this application, the preparation method of the graphite composite anode material described in this application will now be described in detail through the following embodiments.

[0060] Example 1

[0061] 5.5 g of spherical graphite and 5.375 g of SnO2 were dispersed in 15 mL of concentrated sulfuric acid (98% by mass) and stirred in an ice-water bath for 5.5 h to ensure homogeneity. 2.6 mL of hydrogen peroxide (35% by mass) was slowly added, and stirring continued for 5 min. The mixture was then placed in a 45 °C oven and allowed to stand for 3 h. After washing with water and filtration, the mixture was dried to obtain a tin dioxide / micro-expansion modified graphite intermediate. The obtained intermediate was placed in an alkaline aqueous solution of dopamine and stirred for 5 h, then centrifuged. The precipitate was then subjected to carbonization treatment in a tube furnace under an argon atmosphere at 555 °C for 2 h to obtain a carbon-coated / tin dioxide micro-expansion modified graphite composite anode material.

[0062] Figure 2 This image shows a low-magnification scanning electron microscope (SEM) image of the graphite composite anode material in an embodiment of the present invention. Figure 3The image shows a high-magnification scanning electron microscope (SEM) image of the graphite composite anode material in an embodiment of the present invention. The graphite composite anode material, conductive carbon black, and PVDF were uniformly mixed in NMP at a mass ratio of 8:1:1 to form a slurry, which was then coated onto copper foil. After drying, rolling, and stamping, a lithium-ion battery anode sheet was obtained. This anode sheet was then combined with a lithium sheet to form a lithium-ion half-cell. Using 1M LiPF6 as the organic electrolyte, the half-cell was assembled into a 2532 coin cell and subjected to constant current charge-discharge testing.

[0063] Figure 4 This illustrates the graphite composite anode material in an embodiment of the present invention at a capacity of 155 mAh g. -1 Electrochemical performance curves at current density; Figure 5 The graphite composite anode material in an embodiment of the present invention is shown in a 1555 mAh g⁻¹ solution. -1 Cyclic curves at current density. For example... Figure 4 As shown, at 155mA g -1 The initial discharge capacity at the specified current density is 834.6 mAh g. -1 The charging capacity is 625.3mAh g. -1 The initial Coulomb efficiency was 75%.

[0064] Example 2

[0065] 5.5 g of flake graphite and 5.625 g of SnO2 were dispersed in 15 mL of concentrated sulfuric acid (98% by mass) and stirred in an ice-water bath for 5.5 h to ensure homogeneity. 2.6 mL of hydrogen peroxide (35% by mass) was slowly added, and stirring continued for 5 min. The mixture was then placed in an oven at 25°C to 55°C and allowed to stand for 3 h to obtain a tin dioxide / micro-expansion modified graphite intermediate. The obtained intermediate was placed in an alkaline aqueous solution of dopamine and stirred for 5 h, then centrifuged. The precipitate was then subjected to carbonization treatment in a tube furnace under an argon atmosphere at 555°C for 2 h to obtain a carbon-coated / tin dioxide micro-expansion modified graphite composite anode material.

[0066] Composite anode material, conductive carbon black, and PVDF were uniformly mixed in NMP at a mass ratio of 8:1:1 to form a slurry. This slurry was coated onto copper foil, and after drying, rolling, and stamping, a lithium-ion battery anode sheet was obtained. This sheet was then combined with a lithium foil to form a lithium-ion half-cell. Using 1M LiPF6 as the organic electrolyte, a 2532 coin cell was assembled and subjected to constant current charge-discharge testing at 155 mA·g. -1 The initial discharge capacity at the specified current density is 946.6 mAh·g. -1 The charging capacity is 752.7mAh·g -1 The initial Coulomb efficiency was 74.2%.

[0067] Example 3

[0068] 5.5 g of flake graphite and 1.5 g of SnS2 were dispersed in 15 mL of concentrated sulfuric acid (98% by mass) and stirred in an ice-water bath for 5.5 h to ensure homogeneity. 2.6 mL of hydrogen peroxide (35% by mass) was slowly added, and stirring continued for 5 min. The mixture was then placed in a 45 °C oven and allowed to stand for 3 h. After washing with water, filtration, and drying, the tin disulfide / micro-expansion modified graphite composite material was obtained.

[0069] The obtained intermediate was placed in an alkaline aqueous solution of dopamine and stirred for 5 hours, then centrifuged. The precipitate was placed in a tube furnace under an argon atmosphere for carbonization treatment at a temperature of 655℃ for 2 hours to obtain a carbon-coated / tin disulfide micro-expansion modified graphite composite anode material.

[0070] Composite anode material, conductive carbon black, and PVDF were uniformly mixed in NMP at a mass ratio of 8:1:1 to form a slurry. This slurry was coated onto copper foil, and after drying, rolling, and stamping, a lithium-ion battery anode sheet was obtained. This sheet was then combined with a lithium foil to form a lithium-ion half-cell. Using 1M LiPF6 as the organic electrolyte, a 2532 coin cell was assembled and subjected to constant current charge-discharge testing. At 155 mAg... -1 The initial discharge capacity at the specified current density is 955.6 mAh g. -1 The charging capacity is 662.8mAh g. -1 The initial Coulomb efficiency was 73.6%.

[0071] Example 4

[0072] 5.5 g of spherical graphite and 5.3 g of SiO were dispersed in 15 mL of concentrated sulfuric acid (98% by mass) and stirred in an ice-water bath for 5.5 h to ensure homogeneity. 2.6 mL of hydrogen peroxide (35% by mass) was slowly added, and stirring continued for 5 min. The mixture was then placed in a 45 °C oven and allowed to stand for 2 h. After washing with water and filtration, the mixture was dried to obtain a silica / micro-expansion modified graphite intermediate. The obtained intermediate was placed in an alkaline aqueous solution of dopamine and stirred for 5 h, then centrifuged. The precipitate was then subjected to carbonization treatment in a tube furnace under an argon atmosphere at 855 °C for 2 h to obtain a carbon-coated / silica micro-expansion modified graphite composite anode material.

[0073] The composite negative electrode material was uniformly mixed with conductive carbon black, CMC and SBR in deionized water at a mass ratio of 8:1:5.5:5.5 to form a slurry. The slurry was coated on copper foil and then dried, rolled and stamped to obtain a lithium-ion battery negative electrode sheet. The negative electrode sheet was then combined with a lithium sheet to form a lithium-ion half-cell. Using LiPF6 as the organic electrolyte, the half-cell was assembled into a 2532 coin cell and subjected to constant current charge and discharge tests.

[0074] Figure 6 The graphite composite anode material in Example 4 of this invention is shown in 155 mAh g.-1 Electrochemical performance curves at current density; Figure 7 The graphite composite anode material in Example 4 of this invention is shown in a 1555 mAh g⁻¹ solution. -1 Cyclic curves at current density, such as Figure 6 As shown, at 155mA g -1 The initial discharge capacity at the specified current density is 1148.7 mAh g. -1 The charging capacity is 847.9mAh g. -1 The initial Coulomb efficiency was 73.8%.

[0075] Example 5

[0076] 5.5 g of flake graphite and 5.55 g of nano-Si powder were dispersed in 15 mL of concentrated sulfuric acid (98% by mass) and stirred in an ice-water bath for 1 h to ensure homogeneity. 2.6 mL of hydrogen peroxide (35% by mass) was slowly added, and stirring continued for 5 min. The mixture was then placed in a 45 °C oven and allowed to stand for 3 h. After washing with water, the mixture was filtered and dried to obtain a silicon / micro-expansion modified graphite intermediate. The obtained intermediate was placed in an alkaline aqueous solution of dopamine and stirred for 5 h, then centrifuged. The precipitate was carbonized in a tube furnace under an argon atmosphere at 855 °C for 2 h to obtain a carbon-coated / silicon micro-expansion modified graphite composite anode material.

[0077] The composite negative electrode material was uniformly mixed with conductive carbon black, CMC and SBR in deionized water at a mass ratio of 8:1:5.5:5.5 to form a slurry. The slurry was coated on copper foil and then dried, rolled and stamped to obtain a lithium-ion battery negative electrode sheet. The negative electrode sheet was then combined with a lithium sheet to form a lithium-ion half-cell. Using LiPF6 as the organic electrolyte, the half-cell was assembled into a 2532 coin cell and subjected to constant current charge and discharge tests. Figure 8 The graphite composite anode material in Example 5 of this invention is shown in 155 mAh g. -1 Electrochemical performance curves at current density; such as Figure 8 As shown, at 155mA g -1 The initial discharge capacity at the specified current density is 1538.2 mAh g. -1 The charging capacity is 898.3mAh g. -1 The initial Coulomb efficiency was 86.5%.

[0078] Comparative Example 1

[0079] Spherical graphite (17 μm particle size), conductive carbon black, and PVDF were uniformly mixed in NMP at a mass ratio of 8:1:1 to form a slurry. This slurry was coated onto copper foil, and after drying, rolling, and stamping, a lithium-ion battery negative electrode sheet was obtained. This negative electrode sheet was then combined with a lithium foil to form a lithium-ion half-cell. Using 1M LiPF6 as the organic electrolyte, a 2532 coin cell was assembled and subjected to constant current charge-discharge testing at 155 mA g. -1 The initial discharge capacity at the specified current density is 459.4 mAh g. -1 The charging capacity is 344.2mAh g. -1 The initial Coulomb efficiency was 84.1%.

[0080] As can be seen from Examples 1-5 and Comparative Example 1, the graphite composite anode material obtained by the method provided by the present invention allows tin-based or silicon-based materials to be inserted into the interlayer of micro-expanded modified graphite and adhered to the surface of the micro-expanded modified graphite. This effectively solves the dispersion problem of tin-based or silicon-based materials, avoids agglomeration during cycling, and the sandwich structure can alleviate the volume expansion of tin-based or silicon-based materials during charging and discharging and provide the necessary space for their expansion. Further carbon coating can effectively reduce the direct contact between the active material in the carbon anode material and the electrolyte in the battery, avoid electrochemical side reactions between the active material and the electrolyte that would lead to consumption, improve cycle performance and initial coulombic efficiency, and maintain the stability of the material structure.

[0081] The above provides a detailed description of the graphite composite anode material, its preparation method, and its application. Specific examples have been used to illustrate the principles and implementation methods of the present invention. The descriptions of the above embodiments are only for the purpose of helping to understand the method and core ideas of the present invention. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of the present invention. Therefore, the content of this specification should not be construed as a limitation of the present invention.

Claims

1. A method for preparing a graphite composite anode material, characterized in that, The preparation method includes the following steps: S1. Under ice-water bath conditions, graphite, tin-based materials and concentrated sulfuric acid are mixed to obtain a mixed slurry; S2. Add hydrogen peroxide dropwise to the mixed slurry, stir evenly, place it in an oven at 25℃-50℃ and let it stand for 3h-10h, then wash with water, filter and dry to obtain an intermediate containing tin-based material between graphite flakes. S3. After thoroughly mixing the intermediate containing tin-based material between the graphite flakes with the coating material, carbonize and cool to obtain a graphite composite anode material. In step S1, the graphite is flake graphite; The tin-based material is tin disulfide or tin dioxide; The coating material is one or more of polydopamine, polyvinylpyrrolidone, asphalt, and graphene oxide; In step S1, the mass ratio of graphite to tin-based material is 1:0.1-1; The mass-to-volume ratio of the graphite to the concentrated sulfuric acid is 1g:5mL-20mL; In step S2, the volume ratio of concentrated sulfuric acid to hydrogen peroxide is 1:0.1-0.

4.

2. The preparation method according to claim 1, characterized in that, The flake-like graphite is natural flake graphite.

3. The preparation method according to claim 1, characterized in that, The flake-like graphite is spherical graphite formed by spherizing natural flake graphite.

4. The preparation method according to claim 1, characterized in that, In step S3, the coating material accounts for 1%-50% of the mass of the graphite composite anode material obtained after coating.

5. The preparation method according to claim 1, characterized in that, In step S3, the carbonization temperature is 400℃-1000℃ and the carbonization time is 1h-3h.

6. A graphite composite anode material, characterized in that, The graphite composite anode material is prepared by the preparation method according to any one of claims 1-5.

7. An application of a graphite composite anode material, characterized in that, The graphite composite anode material prepared by any of the preparation methods described in claims 1-5 is applied to lithium-ion batteries.

Citation Information

Patent Citations

  • Carbon cage silicon-graphite composite material and preparation method thereof

    CN110697702A